Architecture of the botulinum neurotoxin complex: a molecular machine for protection and delivery. (April 2015) - Lam, Kwok-Ho; Jin, Rongsheng
Highlights: Botulinum neurotoxins are highly potent oral toxins. The large progenitor complex of BoNT is a bimodular 14-subunit complex. NTNHA protects BoNT in the acidic and protease-rich gastrointestinal tract. The HA complex displays multivalent binding with the host glycans in the intestine. The HA complex hijacks E-cadherin to cross epithelial cell junctions. Abstract : Botulinum neurotoxins (BoNTs) are extremely poisonous protein toxins that cause the fatal paralytic disease botulism. They are naturally produced in bacteria with several nontoxic neurotoxin-associated proteins (NAPs) and together they form a progenitor toxin complex (PTC), the largest bacterial toxin complex known. In foodborne botulism, the PTC functions as a molecular machine that helps BoNT breach the host defense in the gut. Here, we discuss the substantial recent advance in elucidating the atomic structures and assembly of the 14-subunit PTC, including structures of BoNT and four NAPs. These structural studies shed light on the molecular mechanisms by which BoNT is protected against the acidic environment and proteolytic destruction in the gastrointestinal tract, and how it is delivered across the intestinal epithelial barrier.